Preparation and characterization of nano-crystalline LiCoVO4 and LiNiVO4 used as cathodes for lithium ion batteries - Phuruangrat A. (2014)
Nano-crystalline LiCoVO4 and LiNiVO4 were prepared using Li2CO3, Co(NO3)2· 6H2O or Ni(NO3)2·6H2O and NH4VO3 as raw materials in deionized water and tartaric acid as a complexing reagent, and followed by 450-600°C calcination for 12 h. TGA showed weight loss due to the combustion of the precursor at 190-500°C. The products were characterized by XRD and found to be LiCoVO4 and LiNiVO4 with an inverse spinel structure. FTIR and Raman analyses showed the V-O stretching vibration of VO4 tetrahedrons and Li-O bending vibration of LiO6 octahedrons. TEM showed nano-powders of LiCoVO4 and LiNiVO4 which have high specific areas for improving lithium ion migration in lithium ion batteries.